2020
DOI: 10.1038/s41598-020-61102-2
|View full text |Cite
|
Sign up to set email alerts
|

Costs of exploratory behavior: the energy trade-off hypothesis and the allocation model tested under caloric restriction

Abstract: In order to maintain the energy balance, animals often exhibit several physiological adjustments when subjected to a decrease in resource availability. Specifically, some rodents show increases in behavioral activity in response to food restriction; a response regarded as a paradox because it would imply an investment in locomotor activity, despite the lack of trophic resources. Here, we aim to explore the possible existence of trade-offs between metabolic variables and behavioral responses when rodents are fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…This result seems contradictory since it might be expected that tadpoles in the low feed regime would have less energy and hence be less active than well fed tadpoles. A similar increase in the distance travelled under low-energy diets has been found in rodent species which can be attributed to a decrease in basal metabolic rate in order to allow more resources to be allocated to foraging activity (Overton and Williams 2004; Peña-Villalobos et al 2020). As X. leavis are filter feeders, the lower density of food in the low feed treatment may have meant that tadpoles would have had to increase their buccal pumping rate and swim further distances to increase their feed intake (Wassersung and Hoff 1979; Ryerson and Deban 2010).…”
Section: Discussionsupporting
confidence: 57%
“…This result seems contradictory since it might be expected that tadpoles in the low feed regime would have less energy and hence be less active than well fed tadpoles. A similar increase in the distance travelled under low-energy diets has been found in rodent species which can be attributed to a decrease in basal metabolic rate in order to allow more resources to be allocated to foraging activity (Overton and Williams 2004; Peña-Villalobos et al 2020). As X. leavis are filter feeders, the lower density of food in the low feed treatment may have meant that tadpoles would have had to increase their buccal pumping rate and swim further distances to increase their feed intake (Wassersung and Hoff 1979; Ryerson and Deban 2010).…”
Section: Discussionsupporting
confidence: 57%
“…However, if behavior trait stabilities are heritable, they could explain why D. melanogaster strains derived from the same wild population display dramatic differences in their behavior responses to new odor environments [53][54][55] . They may also help us understand how and why starved animals show different degrees of search and exploratory behavior compared to non-starved animals [56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies that examined these relationships were either only looking at DEE versus RMR, RMR versus activity, or did not partition the covariances at the among‐ versus within‐individual levels (e.g. Biro et al., 2020; Careau, 2017; Careau et al., 2015, 2019; Peña‐Villalobos et al., 2020; Timonin et al., 2011). By looking at the slope of the DEE–RMR relationship, we found that the performance model was supported at the among‐individual level, whereas the allocation model applied at the within‐individual level.…”
Section: Discussionmentioning
confidence: 99%